Ministry of Justice is the Main Subject for Implementing Public Administration in Providing Forensic Science Services - О. V. Agapova (Bulletin of Kharkiv National University of Internal Affairs)
The Ministry of Justice of Ukraine has been identified in the article as the main subject of public administration in providing forensic science services for justice according to the current legislation of Ukraine and the provisions of administrative science. The modern system of regulations in providing forensic science services for justice has been analyzed. It allowed us to conclude that ensuring the formation and implementation of the state policy in providing forensic science services for justice of Ukraine belongs to the exclusive competence of the Minister of Justice of Ukraine. It has been discovered that forensic activity is an element, which facilitates to form the provision of forensic science services, the functioning of which is ensured by administrative law during the analysis of scientific attitudes to the problem of defining the understanding of the essence of the concept of "provision of forensic science services". The internal structure of the Ministry of Justice of Ukraine, its structural subdivisions responsible for the organization of providing forensic science services for justice have been studied and the content of administrative processes taking place in providing forensic science services for justice has been revealed. The author has singled out the following structural subdivisions of the Ministry of Justice of Ukraine, which ensure the effective functioning of the sphere of expert support of justice: 1) Directorate of Justice and Criminal Justice; 2) Department of Expert Support of Justice; 3) Department of Registration and Systematization of Regulations, etc. It has been stated that the structure of the headquarters of the Ministry of Justice of Ukraine is hierarchically built, consists of a number of structural units that perform different functions depending on the direction and delegated powers. It has been concluded that the purposeful and coordinated work of departments and divisions of the central office of the Ministry of Justice of Ukraine is aimed at improving the activities of research institutions of forensic examinations, centers and other subjects of forensic activity in accordance with modern standards of management in providing forensic science services for justice.